Peran Kompensasi, Lingkungan Kerja, dan Kepemimpinan Transformasional Terhadap Loyalitas Pegawai - Muhammad Fuad Riyadi (Indonesian Journal of Multidisciplinary on Social and Technology, 2025)
This research aims to determine the role of compensation on employee loyalty, the role of the work environment on employee loyalty, the role of transformational leadership on employee loyalty, and the role of compensation, work environment and transformational leadership together. the same for Employee Loyalty. The research used is quantitative research. This research was conducted at the Yogyakarta City Road Traffic and Transportation Department Office. The number of employees in the office is 107 employees, in calculating the number of respondents in this study using the Slovin Formula which produces 66 respondents. The data collection method uses a questionnaire and is homogeneous or independent. This research uses Data Quality Test, Classic Assumption Test (Normality Test, Heteroscedasticity Test, and Multicollinearity Test), Multiple Linear Regression Analysis and Hypothesis Testing. The results of this research show that the Compensation Variable plays a positive and significant role in Employee Loyalty. Work Environment variables play a positive but not significant role in Employee Loyalty. The Transformational Leadership variable plays a positive and significant role in Employee Loyalty. Compensation variables, work environment and transformational leadership simultaneously (together) play a role in employee loyalty.